Pemahaman Perempuan Muslim di Pedesaan terhadap Isu Halal pada Kosmetik Lokal - Sry Lestari Samosir; Abdul Rahman Matondang (Perbanas Journal of Islamic Economics and Business, 2025)
The issue of halal in cosmetics has become a significant concern among Muslim communities, particularly for women who use cosmetic products for daily needs. This study aims to explore the understanding of Muslim women in Tanjung Selamat Village, Deli Serdang, regarding the concept of halal in local cosmetics. Using a qualitative approach and a phenomenological design, data were collected through in-depth interviews and participatory observations. The findings reveal that religiosity is a key factor influencing the informants' understanding and preferences for halal cosmetics. Social norms play an important role in reinforcing collective consumption patterns, while knowledge about halal certification remains limited to basic aspects, such as raw materials. Preferences for local brands, such as Wardah and Mustika Ratu, are driven by good accessibility and high cultural relevance. This study highlights the importance of community-based halal education to improve halal literacy in rural areas and the need for product innovation to meet the increasingly diverse needs of consumers. The practical implications of this study suggest that local cosmetic producers should strategically integrate cultural and religious values into their marketing efforts to more effectively reach consumer segments in rural areas. The novelty of this study lies in its exploration of rural contexts, which have rarely been the focus of similar research, thereby making a significant contribution to the development of literature on halal consumption.